Evaluation of activities aimed at preventing microbiological risks in dental practice - Jolanta Szymańska; Jolanta Sitkowska (Nofer Institute of Occupational Medicine, 2013)
Background: Microbiological contamination of water in dental unit waterlines (DUWL) creates a risk of cross-infections, and is a source of biological risk factors in the work environment of a dentist. The aim of the study was to evaluate dentists' knowledge on DUWL microbiological contamination and the scope of activities/procedures they undertake to monitor it. Material and Methods: The questionnaire survey was conducted in 2010 among 107 Polish dentists using dental units in everyday clinical practice. Results: It has been found that in their daily practice, dentists do not follow procedures leading to reduction or elimination of microbiological contamination of dental unit reservoir water. They are not aware of microbiological contamination of DUWL that supply working handpieces with water. They are unaware of the principles of dealing with dental water and water supply systems or the health risk posed by microbiological contamination of unit water for a dental team and patients. Conclusions: It is necessary to provide dentists with information on microbiological contamination of water in dental units, on the correct procedures of handling water and waterlines that supply working handpieces with water. Med Pr 2013;64(1):11-17